Problems of teaching Arabic in Indonesian Islamic Schools - Ahmad Maghfurin (Genius Journals, 2023)
There must always be problems in learning any foreign language in this world. Foreign language learners may feel more complexity if they have little to do with the language they are learning. Some influential factors include the distance between the native and target language, the lack of interference between the two, and the low motivation and need to learn it. Therefore, in my opinion, Arabic should not be as difficult as English or other foreign languages for Indonesians. In actual learning practices, it is found that there is low proficiency in Arabic among Indonesian students. That is why there should be further studies to investigate the causes. This research is conducted at MAN 1 Semarang selected purposively. It aims to analyze the source of the problems encountered in learning Arabic in madrasahs and find the best solutions. This research involves some Arabic teachers and students from a selected sample of classes. To ensure data credibility, I use document studies, interviews, and observations to collect relevant data. The collected data are analyzed qualitatively. The findings of this research conclude that the learning problems at MAN 1 Semarang led to low students’ entry behavior, disorientation of learning which gives excessive portions of the reading aspect, the teachers who are too dominant in the class so that students play less of a role in the learning process, and minimal use of the target language as a learning medium
Keywords: Problems; teaching Arabic; Islamic Schools